Effect of the recycled rubber on the properties of recycled rubber/recycled polypropylene blends (2015)
ABSTRACT: This study evaluates the influence of recycled rubber (RR) with a specific particle size in the properties of blends, blended recycled polypropylene/polyethylene (RPP) and RR (RPP/RR). The proportions of RPP/RR employed to obtain the blends were as follows: 90/10 (PP90), 75/25 (PP75), 60/40 (PP60) and 45/55 (PP45). The particle size of the RR employed was 850 µm . The properties of the blends were evaluated by rheometric, thermogravimetric (TGA), differential scanning calorimetric (DSC), scanning electronic microscopy (SEM), density, melt flow index and tensile analysis. The maximum torque increased with the RPP content. By DSC analysis, it was observed that the RPP exhibited two melting temperatures, the first corresponded to low density polyethylene (LDPE) and the second to polypropylene (PP). Furthermore, the RR affected the crystallinity of the RPP. By using SEM and TGA analyses, it was determined that the RPP as well as RR contained fillers. The blend densities were higher than those of RPP. The melt flow index exhibited a trend with the amount of RR.